Implementation of Inclusive Education for Children with Special Needs in Elementary Schools - Fadillah, Lili; Rahayu, Nina; Panjaitan, Chery Julida; Wulandari, Febriyantika (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
The aim of this research is to determine the implementation of inclusive education for children with special needs, determine the supporting factors and obstacles in implementing inclusive education programs and to determine the perceptions of school principals and teachers regarding the implementation of inclusive education for children with special needs at SD Negeri 5 Langsa in the 2023 academic year. /2024. This research uses qualitative descriptive method, the subjects of this research are the principal, class teacher and ABK students in class IV it’s good. Data collection techniques use observation, interviews and documentation. The results of this research obtained the following results: (1) The process of implementing inclusive education for children with special needs at SD Negeri 5 Langsa class IVa has been implemented well by the class teachers, although it has not been carried out perfectly and still needs to be carried out further evaluation. (2) The supporting factor in implementing inclusive education in this school is that the teachers at SD Negeri 5 Langsa have previously been equipped with knowledge about inclusive education through conducted by the education office, support from parents and regular students who can receive it. differences, while the inhibiting factors are the unavailability of special accompanying teachers, and the teacher`s lack of understanding regarding the delivery of certain material. (3) The views of teachers and school principals regarding inclusive education implemented in elementary schools are very good. Teachers and school principals really appreciate the regulations that have been because inclusive education really helps students with special needs get the same services aksis students in general.